Long-term nasolabial outcome and patient satisfaction post unilateral cleft lip repair in patients aged above 14 years in a single center - Al-Chalabi, Muath Mamdouh Mahmod (2023)
Objective: To assess long-term nasolabial outcomes and patient satisfaction in patients who underwent unilateral cleft lip and palate repair surgery by reconstructive science unit and whose current age is 14 years or above. Design: This is a retrospective cross-sectional study among unilateral cleft lip and palate patient data records. Setting: The reconstructive science unit in the Hospital Universiti Sains Malaysia (HUSM). Participants: All the patients who underwent unilateral cleft lip and palate repair by the reconstructive science unit within the first two years of their lives and whose current age is 14 years or above. Their data records were accessed and analyzed. Results: The data records of 50 patients were analyzed, including 13 males (26%) and 37 females (74%). Twenty-eight percent of surgeons and patients opined the nasolabial appearance was satisfactory. There were no surgical modifications or post-operative complications among patients. There was a significant association between the surgeon’s comment and the patient’s satisfaction. Therefore, a surgeon’s comment of acceptable nasolabial appearance has a higher chance of patients reporting satisfaction. Conclusion: The long term evaluation of the nasolabial appearance in individuals with cleft lip and palate following surgical correction will show how satisfactory the surgical outcome was, thereby influencing patient satisfaction. In this study, we recommended evaluating patient satisfaction as the second measure of surgical success. All of these assessments will contribute to enhancing surgical results and the psychological effects on cleft patients.